2006
DOI: 10.1016/j.jcrs.2005.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermal features associated with 2 phacoemulsification machines

Abstract: The machines behaved fundamentally differently, with the Legacy Advantec controlling stroke length and Sovereign controlling a fixed power at any setting. Therefore, workload had a much bigger impact on Legacy Advantec thermal characteristics. Pulsing decreased heat produced directly related to the duty cycle. The most dangerous incision burn scenario is with continuous ultrasound, aspiration blocked, and a heavy workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The percentage of power, however, is not comparable among machines. 1,2 Little is known about actual tip vacuum, which also may not be comparable between machines.…”
mentioning
confidence: 99%
“…The percentage of power, however, is not comparable among machines. 1,2 Little is known about actual tip vacuum, which also may not be comparable between machines.…”
mentioning
confidence: 99%
“…2 Due to the strokelength-determined foot pedal of the Legacy, with increased friction, power is increased to maintain the stroke length and therefore the Legacy had a 62% increase of energy production due to incisional friction. The results were very consistent with the same parameters used for both instruments.…”
Section: Discussionmentioning
confidence: 99%
“…2 For analysis, 2-tailed t tests were used and significance was set at P Z.0008 with a Bonferroni correction (61 comparisons were made).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, [5][6][7][8] we showed how certain adjustable variables, such as the aspiration vacuum, aspiration flow rate, and phaco power, are not comparable among machines. We also found that the machines show considerable variance to surge with Cruise Control, with a small but statistically significant impact on the Sovereign unit (AMO) but not the Millennium peristaltic unit (Bausch & Lomb, Beverly Hills, CA).…”
mentioning
confidence: 87%